Light-soaking tests of zinc oxide photoanodes sensitized with an indoline dye on different transparent conductive substrates - B. Onwona-Agyeman; A. Yaya; G. R. A. Kumara; M. Nakao (AIMS Energy, 2018)
Dye-sensitized solar cells (DSCs) were prepared using porous zinc oxide (ZnO) films on aluminum-doped zinc oxide (AZO) and fluorine-doped tin oxide (FTO) transparent conductive glass substrates. X-ray diffraction measurements revealed that, the porous ZnO films were crystallographically oriented differently on the two transparent substrates. The two DSCs were prepared using metal-free indoline dye as the sensitizer and a liquid electrolyte as the hole conductor. Measurements of the power conversion efficiency of the two DSCs over a period of time showed deterioration in the conversion efficiency of the DSCs with the deterioration being faster in ZnO/FTO than ZnO/AZO. The deterioration is attributed mainly to the decrease in light-harvesting ability of the sensitizer and recombination of photo-excited electrons resulting in the decrease in the short-circuit photocurrent densities and the open-circuit voltages in both DSCs during the light-soaking process.